2007
DOI: 10.1161/hypertensionaha.107.093450
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Receptor Blockade Improves Vasomotor Dysfunction and Vascular Oxidative Stress Early After Myocardial Infarction

Abstract: Abstract-Mineralocorticoid receptor blockade improves mortality early after myocardial infarction (MI). This study investigated the vascular effects of mineralocorticoid receptor blockade in the early phase postinfarction in rats. Starting immediately after coronary ligation, male Wistar rats were treated with placebo or eplerenone (100 mg/kg/d). After 7 days, hemodynamic assessment was performed and endothelial function was determined. Maximum acetylcholineinduced relaxation was significantly attenuated in ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 61 publications
1
42
1
3
Order By: Relevance
“…Basic investigations have shown that eplerenone directly acts on blood vessels and improves endothelial function. 24,25 Just as the hypertensive mechanism mediated by aldosterone and salt is complex, 5 the antihypertensive mechanism of eplerenone may also be multifaceted. Clinical research to date has shown that eplerenone when used alone or with other major antihypertensive drugs achieves excellent antihypertensive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Basic investigations have shown that eplerenone directly acts on blood vessels and improves endothelial function. 24,25 Just as the hypertensive mechanism mediated by aldosterone and salt is complex, 5 the antihypertensive mechanism of eplerenone may also be multifaceted. Clinical research to date has shown that eplerenone when used alone or with other major antihypertensive drugs achieves excellent antihypertensive effects.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in early ventricular remodeling may improve the homogeneity of ventricular conduction and, hence, reduce the likelihood for life-threatening arrhythmias. 34 However, other mechanisms, such as prevention of electric remodeling 35,36 and endothelial dysfunction, 37 may be of particular importance.…”
Section: Fraccarollo Et Al Aldosterone Antagonism Improves Infarct Hementioning
confidence: 99%
“…After that, it was homogenized (KCl 150mmol/L; phenyl-methyl-fluoro-sulfonyl 20mmol/L, 1:100) in the Ultra-Turrax homogenizer. Posteriorly, it was performed a sonification with the Hielscher Ultrasound Technology device 13 .…”
Section: Tissue Collection and Preparationmentioning
confidence: 99%